2008
DOI: 10.2169/internalmedicine.47.0689
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Splenosis with Severe Iron Deposition Presenting with Atypical Magnetic Resonance Images

Abstract: An intrahepatic mass was incidentally found in a 41-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…If the splenic implant is intra-hepatic, CT imaging may show hypodense masses with strong enhancement at the early phase and pooling enhancement at delayed phase [9]. Grande et al described multiple well-demarcated nodules without calcifications, slightly hypodense compared to the liver at non-contrast CT, showing as lobular or oval well-circumscribed structures, hyperdense in the arterial phase and isodense in the portal phase after contrast administration [10].…”
Section: Discussionmentioning
confidence: 99%
“…If the splenic implant is intra-hepatic, CT imaging may show hypodense masses with strong enhancement at the early phase and pooling enhancement at delayed phase [9]. Grande et al described multiple well-demarcated nodules without calcifications, slightly hypodense compared to the liver at non-contrast CT, showing as lobular or oval well-circumscribed structures, hyperdense in the arterial phase and isodense in the portal phase after contrast administration [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound may incidentally show hypoechoic masses on the surface of solid abdominal organs, such as the liver [9] or the kidney [5]. It may also show multiple solid masses with a smooth round or ovoid shape, with a homogeneous echo-texture and a hyperehoic peripheral rim, without specific arterial or venous Doppler signals [10].…”
Section: Discussionmentioning
confidence: 99%
“…39 Pancreatic acini were found intermingled with peribiliary glandular acini in 4% of autopsy livers, probably representing an intrinsic component of these glands. 40 Splenic heterotopia presenting as a mass lesion was reported by Lacerda et al 41 With one exception, 42 the rare cases recently reported are examples of splenosis or subcapsular splenic implants following trauma or surgical splenectomy 43 (see Chapter 16). Thyroid heterotopia has been occasionally encountered ( Fig.…”
Section: Heterotopias Of the Livermentioning
confidence: 97%